Evolution of the concept of dystonia - Carlos Henrique F. Camargo; Hélio Afonso G. Teive (Arquivos de Neuro-Psiquiatria)
The term dystonia was proposed by Hermann Oppenheim in 1911, but reports of cervical dystonia are finding since the Roman Empire. The differentiation of the dystonia between a neurological and a psychiatric disease turned a lot. Sometimes was proposed, further, the exclusion of the dystonia as a different phenomenon among the movement disorders. The hypothesis of emotional etiology of the dystonias increase in the decade of 1960 and the conclusion of the etiology of dystonia only happened in the decades of 1970 and 1980 with a series of works of Charles David Marsden. These researches defined dystonia as a movement disorder caused by lesion in the basal ganglia. In February of 1984, a committee of members of Scientific Advisory Board of the Dystonia Medical Research Foundation developed the definition for dystonia accepts until 2013 when an international committee developed the new concept.